KARAKTERISTIK DAN LANGKAH-LANGKAH METODE PENELITIAN RESEARCH AND DEVELOPMENT (BORG & GALL) DALAM PENDIDIKAN - Atina Husnayayin; Zapia Gustina; Desy Eka Citra Dewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research discusses about research and development method (Research and Development or R&D) using the Borg & Gall approach in the field of education. The R&D method aims to produce new products and test its effectiveness. The development process in this method involves systematic stages such as needs analysis, product design, validation by experts, field trials, revisions, and mass production. This method prioritizes innovation in creating effective solutions to learning problems and improving the quality of education. The distinctive characteristics of this approach are in-depth initial research, development based on findings, testing in real situations, and improvements based on trial results. This research highlights that the R&D method is capable of producing useful products and can be implemented widely in education.